Implementasi Sistem Semantik Pada Perangkat Lampu Rumah Cerdas Berbasis Agen - Agung Prasetio; Sabriansyah Rizqika Akbar; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The IoT device provides the potential for obtaining data contextually, by observing and measuring the physical events occurring in the environment. Smart Home has great interest by IoT device developers. Using a semantic approach to data processing on IoT devices provides the ability to define, modify, and interpret better data. In this research uses Nodemcu ESP8266 as a microcontroller on sensor node and actuator node. Raspberry Pi3 is used as an agent that serves as a router and data collection center. Both devices already support wifi connectivity so as to facilitate the communication process. The sensor node is responsible for collecting data derived from the sensors process of the sensor module, the data obtained is sent to the agent to be initialized and inserted into the ontology. Agent performs the reasoning process to change existing data on the ontology according to the rule created and produce more representative and contextual data. The Actuator node performs a query against the current status of the lamp on the ontology as a reference for the action of switching on or off the lamp. Implementation in the form of lights on and off control system in smart home with semantic approach.